Cardiorespiratory Fitness Is Associated With Cognitive Performance in Older But Not Younger Adults. (20th December 2014) - Hayes, Scott M.; Forman, Daniel E.; Verfaellie, Mieke
Abstract: Objectives: Aging is associated with declines in executive function and episodic memory. Cardiorespiratory fitness (CRF) has been associated with enhanced executive function in older adults (OA), but the relationship with episodic memory remains unclear. The purpose of the study was to examine the relationship between CRF and cognition in young and OA and whether CRF mitigates age-related cognitive decline. Methods: Participants completed exercise testing to evaluate CRF (peak VO 2 ) and neuropsychological testing to assess cognition. Results: In OA, peak VO 2 was positively related to executive function, as well as to accuracy on an experimental face–name memory task and visual episodic memory. In young adults (YA), a relationship between peak VO 2 and cognition was not evident. High-fit OA performed as well as YA on executive function measures. On episodic memory measures, YA performed better than high-fit OA, who in turn performed better than low-fit OA. Conclusions: CRF is positively associated with executive function and episodic memory in OA and attenuates age-related cognitive decline. We provide preliminary support for the age-dependence hypothesis, which posits that cognition and CRF relationships may be most readily observed during lifetime periods of significant neurocognitive development.